Strategic Model for Development Planning of Subdistrict Administrative Organization - Sawasdee, Thanakrit; Vongkamjan, Suphawan; Teawnukultham, Boonsaen (Mediterranean Journal of Social Sciences, 2012)
The research objectives were 1) to create the strategic model for development planning of Subdistrict AdministrativeOrganization (SAO), and 2) to experiment the strategic model for development planning of SAO. In this study had introduced the idea offive steps of development strategy combined with other theories and principle related to study strategic model for development planningof SAO. The participants were 221 peoples. Descriptive statistics was percent (%), mean ( X) and standard deviation (S.D.). Theinferential statistics Paired t-test was used for means comparison between before and after implementation achievement. The resultswere as followings : Planning, Plan Implementation, Monitoring and Evaluation, Correcting, Adding and Changing, and Thinking Model ofDevelopment Strategy after implementation, the knowledge development strategy of participants ( X=7.20, 6.91, 6.78, 6.80, and 6.75),were higher than before implementation ( X=5.64, 4.85, 4.60, 4.52 and 4.42), therefore, the mean score of after implementationachievement was higher than before implementation with statistically significant at level of .01. 2). Satisfaction toward the implementationof the strategic model for development planning of SAO as a whole, had average with 4.23 at high level. The strategic model fordevelopment planning of SAO, in case of Keoychai SAO had derived from process with integration of idea of five steps of developmentstrategy combined with other related theories that can be actual use effectively to be a guideline for analysis the implementation created9 steps for conducting in this research that help to initiate results of oriented models for the preparation of development plans of the SAOcan be effectively implemented and successfully achievement, therefore SAO can make a good and suitable plan for the preparation oflocal development plans.